A New Insight into the Electronic Structure Property Relationships in Glassy Ti-Zr-Nb-(Cu,Ni,Co) Alloys - Marko Kuveždić; Mario Basletić; Emil Tafra; Krešo Zadro; Ramir Ristić; Damir Starešinić; Ignacio Alejandro Figueroa; Emil Babić (Metals)
In this work we revisit a vast amount of existing data on physical properties of Ti-Zr-Nb-(Cu,Ni,Co) glassy alloys over a broad range of concentrations (from the high-entropy range to that of conventional Cu-, Ni- or Co-rich alloys). By using our new approach based on the total content of late transition metal(s), we derive a number of physical parameters of a hypothetical amorphous TiZrNb alloy: lattice parameter <semantics>a=(3.42±0.02)</semantics> Å, Sommerfeld coefficient <semantics>γ=6.2<mspace width="0.166667em"></mspace>mJ/mol<mspace width="0.166667em"></mspace></semantics><semantics>K2</semantics>, density of states at <semantics>N(EF)=2.6<mspace width="0.166667em"></mspace>(at<mspace width="4.pt"></mspace>eV)−1</semantics>, magnetic susceptibility <semantics>(2.00±0.05)<mspace width="0.166667em"></mspace></semantics>mJ/<semantics>T2<mspace width="0.166667em"></mspace></semantics>mol, superconducting transition temperature <semantics>Tc=(8±1)<mspace width="0.166667em"></mspace></semantics>K, upper critical field <semantics>μ0Hc2(0)=(20±5)<mspace width="0.166667em"></mspace></semantics>T, and coherence length <semantics>ξ(0)=(40±3)<mspace width="0.166667em"></mspace></semantics>Å. We show that our extrapolated results for the amorphous TiZrNb alloy would be similar to that of crystalline TiZrNb, except for superconducting properties (most notably the upper critical field <semantics>Hc2(0)</semantics>), which might be attributed to the strong topological disorder of the amorphous phase. Also, we offer an explanation of the discrepancy between the variations in <semantics>Tc</semantics> with the average number of valency electrons in neighboring alloys of 4d transition metals and some high-entropy alloys. Overall, we find that our novel method of systematic analysis of results is rather general, as it can provide reliable estimates of the properties of any alloy which has not been prepared as yet.